RELATIONSHIP BETWEEN KNOWLEDGE AND TODDLER MOTHERS' PARTICIPATION IN POSYANDU ACTIVITIES IN KALIJAYA VILLAGE, TELAGASARI DISTRICT, KARAWANG REGENCY - Destiniasari, Lusi; Barkah, Asep (HEARTY, 2024)
Integrated Service Post is a Community-Resourced Health Effort implemented by, from, and with the Community to empower and make it easier for the Community to obtain health services for mothers, infant, and toddlers. The aim is to discover the relationship between knowledge about Posyandu and the participation of toddler mothers in Posyandu activities—chi-square research design with the design of distributing questionnaires directly to respondents. Researchers will collect data using a questionnaire. The total population was 88 respondents, using total sampling. Based on statistical tests, it shows that Posyandu knowledge has a p-value of 0.000 < 0.05. There is a significant relationship between Posyandu knowledge and the participation of mothers of toddlers in Posyandu activities in Kalijaya Village, Telagasari District, Karawang Regency.